Dental Pulp Stem Cell Recruitment Signals within Injured Dental Pulp Tissue - Charlotte Rombouts; Charlotte Jeanneau; Athina Bakopoulou; Imad About (MDPI AG, 2016)
The recruitment of dental pulp stem cells (DPSC) is a prerequisite for the regeneration of dentin damaged by severe caries and/or mechanical injury. Understanding the complex process of DPSC recruitment will benefit future in situ tissue engineering applications based on the stimulation of endogenous DPSC for dentin pulp regeneration. The current known mobilization signals and subsequent migration of DPSC towards the lesion site, which is influenced by the pulp inflammatory state and the application of pulp capping materials, are reviewed. The research outcome of migration studies may be affected by the applied methodology, which should thus be chosen with care. Both the advantages and disadvantages of commonly used assays for investigating DPSC migration are discussed. This review highlights the fact that DPSC recruitment is dependent not only on the soluble chemotactic signals, but also on their interaction with neighboring cells and the extracellular matrix, which can be modified under pathological conditions. These are discussed to explain how these modifications lead to the stimulation of DPSC recruitment.